Flocks and herds between thermalisme and prophecy - Bassani, Maddalena (Gerión. Revista de Historia Antigua, 2013)
Starting from the survey of thermo-mineral sites from the Roman age in the Italian peninsula, this article aims at interpreting some examples of animal ex-votos found among the offerings in some ancient healing stations, as thanksgiving for the animals’ recovery. Such hypothesis is based both on archaeological and epigraphic data, and on post-ancient historical evidences, as well as on legends and pseudoetymology, and on elements pertaining to transhumance. Finally, such objects are set within a frame of reference on worship, inspired by the documentation on Apollo’s shrine at Delphi.